2018
DOI: 10.1155/2018/8269384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Waviness on the Nonlinear Vibration of Gas Lubricated Bearing‐Rotor System

Abstract: This paper presents the effects of the surface waviness on the nonlinear dynamic performance of a gas bearing-rotor system. The coupled vibration with the elastomer is taken into consideration to fit the actual engineering application. The effects of the directions, the amplitudes, and the numbers of waves to the nonlinear dynamic performance are investigated. The results show that the existence of the surface waviness in the circumferential direction can improve the stability of the system obviously. But the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…We integrate the oil film pressure p twice along the bearing surface to obtain the nonlinear oil film forces. 30 Moreover, we consider the influence of the pitch motion, as the rotor is tilted in the bearings, the oil film forces in the bearings are different. In the positive direction of the z 1 axis, the nonlinear oil film forces are as follows:where…”
Section: Mathematical Modelmentioning
confidence: 99%
“…We integrate the oil film pressure p twice along the bearing surface to obtain the nonlinear oil film forces. 30 Moreover, we consider the influence of the pitch motion, as the rotor is tilted in the bearings, the oil film forces in the bearings are different. In the positive direction of the z 1 axis, the nonlinear oil film forces are as follows:where…”
Section: Mathematical Modelmentioning
confidence: 99%
“…How to establish an accurate prediction model of acoustic meta-material performance is a difficult point in the design of acoustic meta-material. At present, scholars such as Li et al [19] have conducted relevant research on the problem of underwater radiation noise in the low-frequency domain of JC using a standard numerical calculation method based on the acoustic solid coupling dynamic equation. The study found that compared to the fluid solid coupling, the acoustic solid coupling mode has the advantages of low modeling difficulty and high model accuracy, making it the preferred algorithm for the numerical calculation of JC underwater acoustic radiation prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Rasheed 4 presented the influences of the circumferential, axial, and combined surface waviness on the journal bearing performance. Li et al 5 and Wang et al 6,7 investigated the effect of waviness on the nonlinear dynamic performance of aerostatic journal bearings and gas lubricated bearing-rotor system in the circumferential and axial directions. They concluded that the wave amplitudes can significantly change the load distribution and dynamics of the bearings.…”
Section: Introductionmentioning
confidence: 99%
“…In those waviness models, the waviness forms were established by the sinusoidal function. 59 Moreover, Ono and Takahasi, 10 Shelly and Ettles, 11 and Tønder 12 also contributed to the bearing surface waviness modeling and its effects on the bearing load capacity and vibrations. The waviness could change the contact condition of the bearing and lead to abnormal vibrations.…”
Section: Introductionmentioning
confidence: 99%